Perbandingan penerapan yurisprudensi di Indonesia dan Australia - Syayyidah, Liza Elyvia Nur (Maliki Interdisciplinary Journal, 2024)
Every country must have a legal system that is used, whether in the form of civil law or common law. Both systems use jurisprudence as a source of law when resolving cases in court. This research aims to examine the comparison of the application of jurisprudence in Indonesia which adheres to a civil law legal system and in America which adheres to a common law legal system. In writing this article, the author used the literature study method. Literature in the form of previous works that contain relevant facts. The facts collected from literature studies are then analyzed to obtain the conclusions or answers you want to reach. Legislative provisions are the main source of law in civil law law, but jurisprudence is also equally important in the application of law in civil law. At the same time, under the common law system, jurisprudence is the product of judicial decision-making in the resolution of legal disputes, with judges “made by law” or subject to the binding force of precedent.